Factors of the Service Marketing Mix Considered by Students in Choosing a University (A Case Study at Universitas Lamappapoleonro Soppeng) - Amrial Amrial; Puji Rahmah; Asnia Minarti; Surianti Surianti (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Lamappapoleonro, 2026)
Competition among universities is increasingly intense, making it essential to understand the factors that influence prospective students’ decisions. This study aims to analyze the factors of the service marketing mix considered by students when choosing Universitas Lamappapoleonro Soppeng. The research employs a quantitative approach with a descriptive-analytical design. The population consists of all active students at Universitas Lamappapoleonro Soppeng, and samples were selected using purposive sampling. Data were collected through questionnaires measuring students’ perceptions of service marketing mix elements, namely product, price, place, promotion, people, process, and physical evidence. Data analysis was conducted descriptively and inferentially using simple linear regression analysis. The results indicate that all elements of the service marketing mix significantly influence students’ university choice, with price, promotion, and people being the most dominant factors. These findings suggest that effective management of the service marketing mix can enhance the university’s attractiveness to prospective students and foster student loyalty